The positions of the scholars of hadith and scientists that used ijtihad (The comparative analisis (Journal of Oriental Studies, 2017)
The method used by the Prophet Muhammad and his sahabas’ duringtheir lifetimes is called “roy” which means “the final decision, the opinion,which could come after reflection, meditation and much effort on finding theright solution”.It was also used during Taabi’een and by Hadith scholars and“Ashab-roy”. However, despite this, pointing out that the debate continued,these differences resulted in the fact that the Hijaz school was related to Hadithscholars and Iraqi school - to “Ashab-roy.” The existence of these twoschools is a historical fact. However, this classification does not correspondto the scientific truth. In the article the Islamic scientists which are calledscholars of hadith and scientists that used ijtihad are considered.